1991
DOI: 10.1007/bf02381180
|View full text |Cite
|
Sign up to set email alerts
|

Homosexual behaviour in wild white-handed gibbons (Hylobates lar)

Abstract: ABSTRACT. Homosexual mounting in apes and prosimians is rare. Male-male mounting was observed between .an adult male white-handed gibbon and an adolescent male in the same group. The behaviour is discussed in terms of the gibbon group's social structure and the development of the adolescent. It is suggested that this behaviour provides reassurance for the adolescent gibbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Edwards and Todd (1991) observed 55 episodes between a father and adolescent son, which were always without tension or aggression, andinitiated by both. The sexualbehavior seemed to provide reassurance to the adolescent Siamangs (Hylobates syndactylus) 2 1 2 Father-sonsexoccurs(likegibbons),butissometimesaccompaniedbythreats,whenthe younger partner wants to end it before the older one does (unlike gibbons) (Bagemihl, 1999) Old World Monkeys…”
Section: Synthesismentioning
confidence: 94%
“…Edwards and Todd (1991) observed 55 episodes between a father and adolescent son, which were always without tension or aggression, andinitiated by both. The sexualbehavior seemed to provide reassurance to the adolescent Siamangs (Hylobates syndactylus) 2 1 2 Father-sonsexoccurs(likegibbons),butissometimesaccompaniedbythreats,whenthe younger partner wants to end it before the older one does (unlike gibbons) (Bagemihl, 1999) Old World Monkeys…”
Section: Synthesismentioning
confidence: 94%
“…In a review of gibbon/siamang sexuality, Bagemihl noted that bisexual incestuous relations between parents and children and among siblings are not uncommon (see also Edwards & Todd, 1991). Dixson (1998), in a review of primate sexuality, reported that sociosexual behavior such as mounting, presentation, mutual embracing, and genital inspection or manipulation begins in infancy in many monkeys and the great apes though males show higher frequencies of some of these behaviors than females.…”
Section: How Nonhuman Primates Learn About Sexmentioning
confidence: 97%
“…There are 2 other accounts of homosexual behavior in gibbons: 1 from wild lar gibbons (Edwards and Todd, 1991), and 1 from captive siamangs (Fox, 1977). Edwards and Todd (1991) described the homosexual behavior between a male and his son as having a reassurance function. Interestingly, the immature male in our study exclusively sang the female song until age 6.4 yr.…”
Section: Constraints Of Captivity On Sexual Behaviormentioning
confidence: 98%